Combined effects of soil amendents and effective microbial agents on container seedling growth and incidence of citrus canker (Bangladesh Journal of Botany, 2025)
To investigate the combined effects of soil amendments and effective microbial agents for the cultivation of container-planted citrus seedlings, Citrus reticulata Ehime 28 was used as the test material. Bentonite clay and attapulgite were mixed with natural soil, and effective microbial agents were then added. The combination comprising attapulgite, bentonite, and effective microbial agents could reduce the soil bulk density and increase the total porosity, pH and EC values, and contents of Olsen-P and Olsen-K in the soil. The combination contains 60% natural soil, 10% attapulgite, 30% bentonite, and 300 times the amount of EM microbial agents significantly promoted the growth of citrus leaves and the formation of chlorophyll; was beneficial to the biomass accumulation of the plants; and promoted the uptake of total nitrogen, phosphorus, and potassium. The incidence of cankers on plant leaves was significantly reduced. This combination has the potential to improve the efficiency of nurseries in producing healthy citrus container seedlings.Bangladesh J. Bot. 54(3): 657-665, 2025 (September) Special